Clinical impact of p16 positivity in nasopharyngeal carcinoma. Issue 4 (14th June 2022) - Shimizu, Yuri; Murakami, Naoya; Mori, Taisuke; Takahashi, Kana; Kubo, Yuko; Yoshimoto, Seiichi; Honma, Yoshitaka; Nakamura, Satoshi; Okamoto, Hiroyuki; Iijima, Kotaro; Takahashi, Ayaka; Kaneda, Tomoya; et al.
Abstract: Purpose: The clinical characteristics and prognosis of HPV‐related nasopharyngeal cancer (NPC) remain controversial. The relationship between p16 status and outcome was retrospectively investigated in the NPC patients. Materials and Methods: Between May 2009 and May 2019, 81 NPC patients who received definitive radiation therapy, in a hospital in Japan, were identified and the prognosis was investigated. p16, p53, and Epstein–Barr virus (EBV) status were assessed. Also, circumferential tumor extent in the nasopharyngeal cavity was assessed on a 5‐point scale. Results: Nine and 72 patients were p16‐positive and p16‐negative, respectively. Fewer patients were EBV‐encoded RNA in situ hybridization (EBER‐ISH)‐positive in the p16‐positive group than in the p16‐negative group ( p  < .01). Seventy‐five patients were nonkeratinizing NPCs, and six patients were keratinizing NPCs. There were two p16‐positive patients among the keratinizing NPCs. The mean circumferential tumor extent scores of 16‐positive and p16‐negative NPCs were 4.2 and 3.2, respectively with a statistically significant difference ( p  = .02). Two‐year progression‐free survival (PFS) of p16‐positive and p16‐negative patients undergoing chemoradiation therapy were 100% and 69%, respectively ( p  = .13). Conclusion: In this study conducted in Japan, p16‐positive NPC patients are minor but not very low, and the proportion of keratinizing NPCs was small. p16‐positive NPCs were seen both in keratinizing and nonkeratinizing NPCs. P16‐positive NPC had a tendency of better PFS than p16‐negative NPC. This better prognosis might be due to the higher radiosensitivity of the p16‐positive cell. Additionally, p16‐positive NPCs seemed to spread more extensively in circumference along the nasopharyngeal mucosa than p16‐negative NPCs. Abstract : The frequency and prognosis of p16‐positive nasopharyngeal carcinoma in Japan, a non‐endemic area for NPC.